2. Use change of variables technique to integrate the following
Z
x(3x − 2) 1
2 dx
"u=3x-2, du=3dx"
"x=\\dfrac{1}{3}u+\\dfrac{2}{3}"
"\\int x(3x-2)^{1\/2}dx=\\dfrac{1}{3}\\int(\\dfrac{1}{3}u+\\dfrac{2}{3})u^{1\/2}du"
"=\\dfrac{1}{3}\\int(\\dfrac{1}{3}u^{3\/2}+\\dfrac{2}{3}u^{1\/2})du"
"=\\dfrac{1}{3}\\bigg(\\dfrac{1}{3}(\\dfrac{2}{5})u^{5\/2}+\\dfrac{2}{3}(\\dfrac{2}{3})u^{3\/2}\\bigg)+C"
"=\\dfrac{2}{45}u^{5\/2}+\\dfrac{4}{27}u^{3\/2}+C"
"=\\dfrac{2}{45}(3x-2)^{5\/2}+\\dfrac{4}{27}(3x-2)^{3\/2}+C"
"=\\dfrac{2}{135}(3x-2)^{3\/2}(9x-6+10)+C"
"=\\dfrac{2}{135}(3x-2)^{3\/2}(9x+4)+C"
Comments
Leave a comment